Re-understanding Tolerance through Intrareligious Dialogue: the Discourse of Anti-Shi'ism in Indonesia - Fany Nur Rahmadiana Hakim (Universitas Islam Negeri Mataram, 2021)
Religious diversity in a country is prone to tensions between groups, especially if there is a very wide disparity between the minority and the majority. Domination by the majority over the minority may lead into discrimination and intolerance. This paper describes how the Islamic discourses of the Muslim majority in Indonesia, represented by Nahdlatul Ulama and Muhammadiyah as the largest Islamic mass organizations in Indonesia, perceive the Shia community. This paper utilizes the concept of communal tolerance developed by Jeremy Menchik to analyze how intolerance is still inherent in amongst the majority groups. Through a descriptive method, this paper refers to many relevant literature reviewed with an intra-religious dialogue approach. Considering the importance of intra-Muslim dialogue as part of attempts to redefine tolerance, discriminatory actions should be no longer experienced by minority groups.